Analisis Tingkat Kondisi Fisik Mahasiswa Prodi Pendidikan Jasmani - Hariadi, Nopi; Nopiana, Rina; Wahyudi, Johan; Arkanudin, Zaenul (Jurnal Sporta Saintika, 2025)
ABSTRACT The purpose of this research is to determine the physical condition level of students in the Physical Education Study Program at Hamzanwadi University. The research method used is descriptive qualitative. The population of this study consists of all students from the 2022 cohort of the Physical Education Study Program, totaling 106 individuals. The sample was determined using simple random sampling, taking a random sample of 15%, which amounts to 16 individuals. The data collection instruments used were flexibility tests (Sit and Reach Test), balance tests (Standing Stork Test), abdominal muscle strength tests (Sit Up and Push Up), strength tests (Standing Long Jump), speed tests (30 m Sprint), agility tests (T-Test), and VO2max endurance tests (Bleep test). Data analysis used quantitative descriptive analysis techniques with percentages. From the research results, it can be concluded that the physical condition of the students in the Physical Education Study Program at Hamzanwadi University can be categorized as "good." The highest percentage of the physical condition level of students from each test item is in the “Very Good” category, which includes the Leg Muscle Explosiveness Test at 100%, the “Good” category for the Agility Test at 62.5%, the “Moderate” category for the Speed Test at 50%, the “Poor” category for the Endurance/Vo2max Test at 62.5%, and the “Very Poor” category for the Static Balance Test at 18.8%. Keywords: Physical Condition, Student